Effect of Betaine Supplementation on Growth Performance and Liver Function Test of Growing Murrah Buffalo Calves - Kumar, Sudhir; Yadav, Satya Prakash; Chandra, Gulab; Sahu, Dev Saran; Kumar, Raj; Maurya, Prem Sagar (Indian Journal of Animal Nutrition, 2022)
This study aimed to observe the effect of betaine (BET) supplementation on the growth, immunity, and blood metabolites of Murrah buffalo calves. Twenty-one Murrah buffalo calves with body weight (BW) (98.70 Â± 1.31 kg) and age (8.12 Â± 0.55 months) were selected and randomly distributed into three groups, 7 calves in each group. The diet of all three groups was the same except that the respective group additionally supplemented with 0, 7, and 14 g/d BET during 90 d of the experiment period. The BW and DMI were recorded on fortnightly intervals. Blood samples were taken on fortnightly intervals for the estimation of liver enzymes. There was an improvement (P